ANALISIS KUANTITATIF KADAR FLAVONOID EKSTRAK ETANOL DAUN BELIMBING WULUH (Averrhoa bilimbi L.) DI BANJARMASIN DENGAN METODE SPEKTROFOTOMETRI UV-VISIBLE - Anna Khumaira Sari; Noverda Ayuchecaria; Dwi Rizki Febrianti; Mochammad Maulidie Alfiannor Saputera; Vitalika Regitasari (Jurnal Insan Farmasi Indonesia, 2019)
One of the plants in Indonesia that can be used as traditional medicine is bilimbi leaves extract (Averrhoa bilimbi L.). Bilimbi leaves are known to contain flavonoids, saponins, and tannins. Flavonoids are one of the compounds that can counteract free radicals that cause degenerative diseases. The purpose of this study was to determine the levels of flavonoids in the ethanol extract of bilimbi leaves. Flavonoid compounds in bilimbi leaves were taken by extracting bilimbi leaves. Bilimbi leaves were extracted using maceration and re-maceration method with ethanol 96%. The determination of flavonoid content begins with a qualitative test, then the flavonoid content is measured using a UV-Visible spectrophotometer method with quercetin standard. The qualitative test results showed that ethanol extract of bilimbi leaves positively contained flavonoids. The quantitative analysis using UV spectrophotometry showed that the flavonoid values in the ethanol extract of bilimbi leaves (Averrhoa bilimbi L.) read at a maximum wave of 412 nm was 42.865 mg / L.